SÍNTESE E CARACTERIZAÇÃO DO CRISTAL TERNÁRIO DE 1,10-FENANTROLINA E GLICINA COMPLEXADO COM COBRE (II) PARA O USO EM ANTITUMORAIS. - OLIVEIRA NETO, João Gomes de (2019)
Considering global deaths high number associated with epidemics caused by neoplastic diseases progression, noted that cancer in recent years presented alarming data and is responsible for a mortality rate higher than other pathologies. High resistance of the human body to drugs, justifies exacerbated increase cancer, this fact dialogues with the antitumor agents non-effectiveness. Therefore, this study aimed the 1,10-Phenanthroline and Glycine complexed copper (II) ternary crystal synthesis, as well the physico-chemical and biological properties study for antitumor activity application. The sample was synthetized by slow evaporation solvent method during 14 days. The obtained crystal was characterized by X-ray Diffraction (XRD) with Rietveld method, Scanning Electron Microscopy (SEM), Energy Dispersion X-ray Spectroscopy (EDS), Visible Ultraviolet Region (UV-Vis) Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, Thermogravimetric Analysis (TG), Differential Thermal Analysis (DTA), Differential Exploration Calorimetry (DSC), Magnetization, Solubility Test and in vitro antitumor activity evaluation. Optical analysis showed ideal pH for sample crystallization is 9.4. SEM and EDS analyzes showed interfacial defects on the crystalline surface and the elemental composition of the sample, respectively. XRD measurements at room temperature (25 °C/298 K), showed that the crystal have monoclinic structure with a P21/n space group containing 4 molecules for unit cell (Z = 4) and lattice parameters: a= 7.041(2) Å, b= 12.246(1) Å, c= 20,194(2) Å and β= 94,869°. FTIR and Raman spectra reveal Cu2+ ion complexation with the organic molecules. Thermoanalytical techniques indicades a phase transformation between 320 and 345 K, which probably occurs due to material dehydration. The XRD as a function of temperature (303 to 373 K) confirmed the material irreversible phase change of the from hydrated form to anhydrous form. Using Le Bail method for structure refinement was possible to determine that the new phase belongs to the monoclinic system (P121 space group) with lattice parameters a= 21,983(5) Å, b= 10,175(2) Å, c= 12,871(2) Å and β= 95,940(1) °. Raman spectroscopy with temperature variation (300 to 355 K) ratified phase transformation verified by XRD, since the crystal external lattice modes underwent changes as a presumed attempt of the molecule to conform to a anhydrous form. Magnetization analyzes revealed that the material has paramagnetic properties with antiferromagnetic short range interactions. The crystal showed an aqueous solubility profile suitable for antitumor reaching 0.1055 g/L in 120 min. Antitumor activity of the 1,10-phenanthroline and glycine complexed copper (II) monocrystal was confirmed by cytotoxic assays in HCT-116 tumor cell line, showing an IC50= 3.73 M, upper to the cisplatin complex (IC50= 5,34 M). The data obtained suggest that the material of this present study is a strong candidate to be employed in therapies aiming regularity in the antitumor activity.